Alves VLS, Feldman LB, organizers. Managers of Health in the Scope of Quality: Acting and Competences, multi-disciplined approach. São Paulo (SP): Martinari; 2011 - Souza, Cláudio José de; Sptiz, Viviane de Moraes; Silvino, Zenith Rosa; Christovam, Bárbara Pompeu (Rev Rene, 2013)
The changes of the contemporaneity demanded that the professionals in the area of health, besides contemplating the scope of care, also absorbed the managing area. The authors of the reviewed work reaffirmed that, in these two decades of XXI century, there is a close relation between care and management.  DOI: https://doi.org/10.15253/2175-6783.20130003000022